A note on Sargan densities - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1987)
This note reexamines the general class of Sargan densities analyzed by Goldfeld and Quandt (1981), Kafei and Schmidt (1985), and others in the context of approximating normal densities in certain econometric models. It suggests a third-order Sargan density which complies with the Goldfeld and Quandt criteria, is unimodal, and is the best approximation to the normal for orders less than or equal to 3. Some errors in Goldfeld and Quandt paper are corrected.